Planning Instructions in Class - Samdani Samdani (Indonesian Journal of Education (INJOE), 2021)
Learning planning is a plan that occurs in the classroom, so without careful planning it can also cause the teaching and learning process to not be as optimal as possible. In this case, the teacher plays an important role so that there is the term competent teacher who is not an expert in teaching but is an expert in all fields of learning.